2024
DOI: 10.1021/acs.est.4c02638
|View full text |Cite
|
Sign up to set email alerts
|

Considerations and Opportunities for Probe Capture Enrichment Sequencing of Emerging Viruses from Wastewater

Rose S. Kantor,
Minxi Jiang

Abstract: Until recently, wastewater-based monitoring for pathogens of public health concern primarily used PCR-based quantification methods and targeted sequencing for specific pathogens (e.g., SARS-CoV-2). In the past three years, researchers have expanded sequencing to monitor a broad range of pathogens, applying probe capture enrichment to wastewater. The goals of those studies included (1) monitoring and expanding fundamental knowledge of disease dynamics for known pathogens and (2) evaluating the potential for ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…In support of this observation, the ratio of target-to-nontarget in the input nucleic acids has previously been shown to affect the success of probe-capture sequencing . Accordingly, measurement of this ratio (via dPCR and/or Qubit) before library preparation and enrichment might be a useful predictor for the success of sequencing . Additional parameters of interest include target virus concentration, nucleic acid integrity, fragment size distribution, and nontarget sequence composition.…”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations
“…In support of this observation, the ratio of target-to-nontarget in the input nucleic acids has previously been shown to affect the success of probe-capture sequencing . Accordingly, measurement of this ratio (via dPCR and/or Qubit) before library preparation and enrichment might be a useful predictor for the success of sequencing . Additional parameters of interest include target virus concentration, nucleic acid integrity, fragment size distribution, and nontarget sequence composition.…”
Section: Resultsmentioning
confidence: 85%
“…However, several studies using the narrower RVOP panel found remarkably high coverages of SARS-CoV-2, surpassing other respiratory human viruses included in the panel. ,, Another study also found that the share of sequences derived from SARS-CoV-2 was higher when using the Respiratory Virus Oligo Panel (RVOP) than the broader Respiratory Pathogen ID/AMR Panel (RPIP), which included other high-abundance targets . Although this high sequencing recovery of SARS-CoV-2 may have been partially due to the higher prevalence at the sampling time, future work is needed to design and benchmark custom probe panels that balance target diversity and sequencing sensitivity for early detection of emerging virus strains …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations